Comparison of cash holding rates in different industries - Dong, Nuomeng (2019)
The study explores the cash holdings among Chinese listed companies. The study was motivated by the reported fact that cash holdings among the companies in developed Western economies maintain surprisingly high cash holdings, and also by the fact that Chinese companies have developed rapidly and successfully compete globally. In the case with the Therefore, cash holdings in Chinese companies could also be solid, and there is need to evaluate determinants of cash holdings in the Chinese companies, as well as to compare the cash holdings across industries. Western companies, the main explanations pertain to the precautionary cash holdings, as well as to agency costs problem. These mechanisms are investigated for Chinese companies in the current study. The goal of the study is to evaluate the relevance of different factors that determine the level of cash holdings for Chinese listed companies. Such analysis requires substantial volume of data. Therefore, the considered sample includes constituents of Shanghai Composite and Shenzhen Composite stock indices; the sample includes years 2011-2018. The methodology of panel data regression and cross-sectional regression analysis is considered. The differences across industries are evaluated in the analysis by using descriptive statistics method, as well as by using industry dummy variables in the regression. The results provide several relevant findings. There re cross-industry differences in the level of cash holding in the Chinese listed firms. The lowest cash holding is among financial and utility companies. While the highest cash holdings levels are among the companies in consumer staples and information technology. The regression analysis results showed that the dividends and financial leverage have negative impact on cash holdings, while cash flow and volatility of cash flow have positive impact. The results are therefore supportive of both considered mechanisms, the precautionary savings hypothesis and also the agency cost of cash flow hypothesis. The results also evidenced negative effect on cash holdings by higher management ownership and institutional ownership.